(untitled) (Research, Society and Development, 2022)
Copaiba oil, which due to its therapeutic properties, has been widely used in the dental routine. The objective of this narrative review was to evaluate the properties of Copaíba oil in laboratory and clinical studies, related to oral bacteria, dental biofilm and tissue healing conditions. Initially, 3480 articles from the following databases were evaluated in this literature review: Pubmed, Lilacs, Scielo, Embase, Web of Science and Cochrane Library, between 1989 and 2021. The search terms were: copaifera oil, copaifera oil and dentistry, copaifera oil and periodontal disease, copaifera oil and caries. The inclusion criteria adopted were: in vitro, animal and human studies performed with any type of Copaifera ssp. Duplicate articles, case reports and studies in languages ​​other than English and Portuguese were excluded. After applying the adopted inclusion and exclusion criteria, 36 articles were evaluated in this literature review. The results showed that copaiba has antimicrobial and anti-inflammatory activity, which gives it promising possibilities for various formulations in oral hygiene. There is a lack of research that really proves the effectiveness of copaiba oil in relation to the specific therapeutic application in dentistry, reflections and debates on the use of phytotherapy in dentistry are necessary, especially in view of the healing, anti-inflammatory and antimicrobial benefits reported in the literature. about copaiba oil but with observational studies so far.